Prevalence of low back pain and its associated factors among doctors in a hospital in Selangor - Lee, K. Y.; B. N., Farhanah; M.H., Rifaaie; Chang, C. Y.; Syed Hassan, Syed Tajuddin; Ariffin, Ahmad Azuhairi (Community Health Society Malaysia, 2014)
Background: Low back pain is relatively a major cause of disability among the working population and has a significant socioeconomic impact. This study was done to determine the prevalence and associated factors of low back pain among doctors in a hospital. Materials and Methods: A cross-sectional study was done to determine the prevalence and associated factors of low back pain among doctors in a hospital in Selangor, Malaysia. Except for one hospital in Kuala Lumpur, no similar study has been done on medical doctors. Respondents’ information include on socio-demographic (age, gender, race and marital status), occupational factors (length of service, average daily working duration, prolonged sitting, prolonged standing, awkward posture, static posture, sudden movement, lifting and forceful movement, physical factors, back care training) and psychosocial factors (job satisfaction, problems with colleagues, problems with employer, boredom in work and stress). Result: There were 63 respondents from 90 (70%) approached, after simple random selected among doctors. The prevalence of low back pain among respondents was 65.1%. There were significant associations (p< 0.05, n=63), between low back pain and race, prolonged sitting, prolonged standing, awkward posture, lifting and forceful movement, and heavy physical work. Conclusion: Since the prevalence was high, training on back care, proper sitting, standing and manual handling should be emphasized to reduce the problem.